The Role of Syk/CARD9-Coupled C-Type Lectin Receptors in Immunity to Mycobacterium tuberculosis Infections - Mohlopheni Jackson Marakalala; Lisa M. Graham; Gordon D. Brown (Clinical and Developmental Immunology)
There is increasing interest in understanding the mechanisms underlying the interactions that occur between Mycobacterium tuberculosis and host innate immune cells. These cells express pattern recognition receptors (PRRs) which recognise mycobacterial pathogen-associated molecular patterns (PAMPs) and which can influence the host immune response to the infection. Although many of the PRRs appear to be redundant in the control of M. tuberculosis infection in vivo, recent discoveries have revealed a key, nonredundant, role of the Syk/CARD9 signalling pathway in antimycobacterial immunity. Here we review these discoveries, as well as recent data investigating the role of the Syk/CARD9-coupled PRRs that have been implicated in mycobacterial recognition, including Dectin-1 and Mincle.